A trajetória do projeto Teletandem Brasil: da modalidade institucional não-integrada à institucional integrada - Cavalari, Suzi Marques Spatti [UNESP] (2014)
The purpose of this paper is to present the road taken by the Teletandem Brasil Project (Telles, 2006) and describe the modifications that have occurred in relation to the implementation of teletandem activities, which implies changes from a non-integrated modality to an integrated one (Brammerts, 1996). In order to do so, a characterization of the initial context assumed by the project is presented – non-integrated institutional teletandem - in contrast with the new environment fostered by a partnership between UNESP (Universidade Estadual Paulista) and UGA (University of Georgia). This new partnership has allowed the inclusion of teletandem into the foreign language syllabus, characterizing the institutional integrated teletandem. We also show the activities derived from this new modality.